2003
DOI: 10.1086/376642
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of Levofloxacin-Resistant Pneumococci in Immunocompromised Adults after Therapy for Community-Acquired Pneumonia

Abstract: We describe 4 patients infected with levofloxacin-resistant pneumococci after therapy for community-acquired pneumonia (CAP). The 4 patients had 15 episodes of CAP; Streptococcus pneumoniae was isolated from blood or sputum samples obtained during 14 of the episodes. The underlying medical condition was Bruton agammaglobulinemia in 3 patients and chronic lymphoid leukemia in the other. The initial episode of CAP in each patient was due to a levofloxacin-susceptible strain. One of 4 reinfections and 5 of 6 rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0
3

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(42 citation statements)
references
References 30 publications
1
38
0
3
Order By: Relevance
“…While the development of fluoroquinolone resistance has been linked with fluoroquinolone use (181), the rates of resistance in S. pneumoniae remain relatively low (Ͻ1% in the United States and Ͻ3% in Europe) (182), although higher rates have been reported in Asia (10.5%) (183,184) and Canada (7.3%) (185). Resistance to fluoroquinolones can also develop during treatment, and there are several reports describing treatment failures in pneumococcal infections where fluoroquinolones were used (186,187). These cases were primarily elderly patients with chronic lung disease, a patient population that is frequently exposed to fluoroquinolones and in which higher rates of resistance have been reported (188).…”
Section: Fluoroquinolone Resistancementioning
confidence: 99%
“…While the development of fluoroquinolone resistance has been linked with fluoroquinolone use (181), the rates of resistance in S. pneumoniae remain relatively low (Ͻ1% in the United States and Ͻ3% in Europe) (182), although higher rates have been reported in Asia (10.5%) (183,184) and Canada (7.3%) (185). Resistance to fluoroquinolones can also develop during treatment, and there are several reports describing treatment failures in pneumococcal infections where fluoroquinolones were used (186,187). These cases were primarily elderly patients with chronic lung disease, a patient population that is frequently exposed to fluoroquinolones and in which higher rates of resistance have been reported (188).…”
Section: Fluoroquinolone Resistancementioning
confidence: 99%
“…There have been multiple reports in the past of resistance development in patients treated with levofloxacin, 6,7 and studies have shown that isolates, susceptible according to nationally accepted breakpoints, can carry first-step parC mutations, 8 which make resistance development on treatment more likely. 9 Yet, in the 2.5 years of this study, we detected only one convincing case of de novo second-step mutation leading to high-level levofloxacin resistance, despite the fact that we managed to capture repeat S. pneumoniae isolates from 32 adult patients.…”
Section: Discussionmentioning
confidence: 99%
“…The first-step parC mutation (Ser79Phe) present in patient A's strain has been reported commonly in the literature, and was present in 47/115 S. pneumoniae strains with levofloxacin MICs 2 mg/L isolated in a Canadian study (the most common parC substitution detected). 7 The main weakness of studies based on laboratory samples is that they represent only a tiny proportion of the overall burden of disease. For most patients with S. pneumoniae infection, the organism is never cultured and resistance development can therefore be difficult to detect.…”
Section: Discussionmentioning
confidence: 99%
“…A diferencia de lo que ocurre con los betalactámicos, en los que las cepas resistentes son casi siempre el resultado de la adquisición de un gen de resistencia antes del inicio del tratamiento, en las fluoroquinolonas es frecuente que la resistencia se desarrolle durante la terapia 49 , lo cual explicaría la existencia de fracasos terapéuticos poco después de su comercialización en zonas con baja prevalencia de resistencias. De hecho, el consumo previo de fluoroquinolonas se ha identificado como un factor de riesgo de colonización e infección por neumococo resistente a levofloxacino (odds ratio [OR], 10,7), al igual que la enfermedad pulmonar obstructiva crónica (EPOC), la estancia en residencia de ancianos y el origen nosocomial de la bacteria 52,53 , razones por las cuales algunos autores recomiendan no utilizarlas de primera elección tanto en pacientes que han recibido previamente fluoroquinolonas como en aquellos diagnosticados de EPOC 49,52 .…”
Section: Fluoroquinolonasunclassified